Equity crowdfunding platforms and social media: a Twitter analysis - Battisti, Enrico; Graziano, Elvira Anna; Christofi, Michael (My University, 2021)
Purpose: The purpose of this study is to explore the central users (hubs) in the dissemination of equity crowdfunding (EC) news on social media, with particular regard to Twitter. Specifically, the study explores some aspects related to the diffusion of news through social networks concerning EC. Design/methodology/approach: Through a social network analysis (SNA) technique the authors define an understanding of the users' network that is created on Twitter when it comes to crowdfunding. Using Twitter data, the authors identify the central actors on the social network that produce and/or disseminate information about crowdfunding tools. Findings: The results indicate that a large number of users tweeted about EC in relation to the introduction of the most important Commissione Nazionale per le Società e la Borsa (Consob) Regulation n. 20264 of 17/01/2018 on an equity model at the beginning of 2018; the growth in the use of this instrument in the first quarter of 2019 and the publication of Commissione Nazionale per le Società e la Borsa (Consob) Regulation n. 21110 of 10/10/2019. Moreover, the authors find that in the case of tweets concerning EC, the operators of the sector, with particular regard to crowdfunding platforms, are central to the network, followed by traditional and specialised media. Originality/value: The results shed new light on a still unexplored research field concerning the diffusion of news about EC from a platform's perspective. To the best of the authors' knowledge, this is the first explorative study that jointly investigates an EC model and social media in the Italian market, considering the impacts of two different and important regulations. In particular, this study contributes to the literature on EC by clarifying some new aspects related to the diffusion of news through Twitter.
Keywords: Equity crowdfunding platforms; Social media; Social network analysis; Entrepreneurial finance; Twitter; Digital transformation